Memory Retrieval of Cultural Event Experiences: Examining Internal and External Influences - Kim, Jong; Jang, S. (SAGE Publications Inc, 2014)
As global competition intensifies, destinations increasingly aim to deliver memorable tourism experiences (MTEs). To ensure that tourists remember past tourism experiences, destination managers and researchers must understand the factors that aid memory recall. Therefore, this research examined the influence of both internal and external factors on tourists’ memory retrieval of cultural events. Specifically, the current study examined the effects of the personality trait of openness to a different culture and retrieval cues (i.e., auditory, olfactory, and memorabilia) on memory retrieval. In two experiments using samples from two different programs at the same cultural event, subjects’ autobiographical memories of the experiences were tested. The results showed that all of the tested factors effectively facilitated memory retrieval. Subjects who were more receptive to different cultures were more likely to recollect and vividly recall the event experiences. Moreover, subjects who were exposed to retrieval cues that were relevant to the themes of the event demonstrated better memory recall. Managerial implications for event organizers are also discussed in this article.